Tingkat Keberhasilan Hidup Dan Laju Pertumbuhan Transplantasi Karang Acropora sp. di Perairan Pantai Dego-dego Kecamatan Bontobahari Kabupaten Bulukumba. - Basda, Putra Astaman; Rauf, Abdul; Yusuf, Kamil (JURNAL ILMIAH WAHANA LAUT LESTARI (JIWaLL), 2025)
Dego-dego Beach, a tourist destination in Darubiah Village, Bontobahari District, Bulukumba Regency, boasts diverse marine biological resources, including a coral reef ecosystem. However, the condition of this coral reef ecosystem is unfortunately degrading due to numerous environmentally unfriendly tourist activities and a lack of awareness regarding the ecosystem's importance. Consequently, coral reef ecosystem restoration efforts, specifically through coral transplantation, are a suitable option for achieving coral reef sustainability. This research aims to determine the survival rate and growth rate of transplanted corals, as well as to assess the environmental parameters of the waters in the Acropora sp. coral transplantation area at Dego-dego Beach in 2024. The research methodology involved direct observation at the Acropora sp. coral transplantation site in 2024, utilizing both primary and secondary data. The study's findings indicate that the survival rate of Acropora sp. coral transplants from 2024 to 2025 reached 70%. The average total growth rate of the transplanted corals after 12 months of planting was 2.44 cm, with an average monthly growth rate of 0.20 cm/month. And factor inhibiting coral fragment growth is the overly dense placement of fragments, leading to nutrient competition. Additionally, suboptimal substrate types that are easily fragmented by currents or waves can cause excessive sedimentation transport, which in turn disrupts the photosynthesis of zooxanthellae.